PENGARUH INSENTIF PAJAK, TINGKAT PENDAPATAN, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM E-COMMERCE - Nitara, Putu Guri; Setiawan, Putu Ery (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023DO - 10.24843/EEB.2023.v12.i10.p06, 2023)
The Covid-19 pandemic has led E-commerce business models become one of the many best selling strategies that has widely adopted by MSMEs. The number of MSME actors that adopted E-commerce business models has increased every year, in contrast their taxpayers’s compliance levels is still low. This study aims to obtain empirical evidence on the effect of tax incentives, income levels and tax socialization on E-commerce MSME taxpayer compliance during the Covid-19 pandemic. This study used purposive sampling method, with a total sample of 97 MSMEs taxpayers who use E-commerce selling strategy and actively registered at KPP Pratama Denpasar Barat. The research method used in this study is multiple linear regression. The results found that tax incentives, income levels, and tax socialization had a significant positive effect on taxpayer compliance among MSMEs in E-commerce business. The theoretical implications of this research are able to support attribution theory and theory of planned behavior, and the practical implications can be taken into consideration in making policies to maximize taxpayer compliance.